Genetic testing for sports performance - Comment: genetic test available for sports performance - Savulescu, J.; Foddy, B. (British Journal of Sports Medicine, 2005)
For the first time, we can now obtain a cheap and non-invasive genetic test, which tells us not if we have a disease or whether we are related to our parents, but what kind of sports we are likely to be good at.